Mine Waste-Based Next Generation Bricks: A Case Study of Iron Ore Tailings, Red Mudand GGBS Utilization in Bricks - M. Beulah; M. R. Sudhir; Mothi Krishna Mohan; G. Gayathri; Deekshith Jain (Advances in Materials Science and Engineering)
Utilization of mine wastes as a building material in the construction industry surmises to environmental and sustainable concepts in civil engineering.The potential environmental threat posed by mining wastes, as well as a growing societal awareness of the need to effectively treat mining wastes, has elevated the subject importance.The present research proposes a method of producing bricks that is both cost effective and environmentally benign. The research is based on the geopolymerization, known to save energy by obviating high-temperature kiln firing and lowering greenhouse gas emissions. The methodology encompasses the mixing of red mud and iron ore tailings in the range of 90% to 50% with a decrement of 10% with GGBS in the range of 10% to 50% with an increment of 10%. The raw materials and the developed composites have been tested as per Indian and ASTM standards.In addition to tests pertaining to the physical and mechanical properties, XRF, XRD, and SEM tests have been performed for examining various related issues. Based on the result analysis, the compressive strength values showed noticeable differences in case of IOT and red mud bricks with IOT-based bricks showing better compressive strengths.